Akibat Hukum Kepemilikan Tanah untuk Rumah Tinggal Berdasarkan Jual Beli yang Melebihi Batas Maksimum (SETARA : Jurnal Ilmu Hukum, 2023)
This article examines the legal consequences of residential land ownership acquired through sale and purchase when the accumulation exceeds the maximum ownership limit permitted by Indonesian land policy. The issue is important because the regulatory framework already requires buyers to declare that their ownership does not exceed the limit, yet in practice large-scale accumulation of residential land still occurs without effective sanctions. Using normative juridical research, the article reviews agrarian statutes, land registration rules, and doctrinal writings on justice and legal sanctions. The study finds that the applicable regime establishes an ownership ceiling through administrative requirements, but it does not provide an explicit sanction structure when the declaration is violated or when excessive ownership is later discovered. This gap weakens enforcement, contributes to inequality in access to housing land, and undermines the social function of land. The article argues that legal certainty requires a firmer sanction model, including administrative disincentives and stronger supervision of transfer registration.
Keywords: Residential Land Ownership; Maximum Ownership Limit; Land Registration; Administrative Sanctions; Legal Certainty